2021
DOI: 10.3389/fevo.2021.767177
|View full text |Cite
|
Sign up to set email alerts
|

11 Pressing Research Questions on How Light Pollution Affects Biodiversity

Abstract: Artificial light at night (ALAN) is closely associated with modern societies and is rapidly increasing worldwide. A dynamically growing body of literature shows that ALAN poses a serious threat to all levels of biodiversity—from genes to ecosystems. Many “unknowns” remain to be addressed however, before we fully understand the impact of ALAN on biodiversity and can design effective mitigation measures. Here, we distilled the findings of a workshop on the effects of ALAN on biodiversity at the first World Biodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
91
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 151 publications
(203 reference statements)
0
91
0
3
Order By: Relevance
“…Most of these studies concerning single light sources showed the impact of three different light parameters: (1) broad spectral distributions, including short, mid, and long wavelengths; (2) illuminance levels below 10 lx, and (3) CCTs of 3300-5300 K. Meanwhile, when multiple light sources were compared, only their spectral power distribution was considered. This supports the need for a consensus on measuring and reporting physical parameters of artificial light sources, as it is necessary to properly address the components of artificial light known to be stressors [273].…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Most of these studies concerning single light sources showed the impact of three different light parameters: (1) broad spectral distributions, including short, mid, and long wavelengths; (2) illuminance levels below 10 lx, and (3) CCTs of 3300-5300 K. Meanwhile, when multiple light sources were compared, only their spectral power distribution was considered. This supports the need for a consensus on measuring and reporting physical parameters of artificial light sources, as it is necessary to properly address the components of artificial light known to be stressors [273].…”
Section: Discussionmentioning
confidence: 78%
“…Yet, the light sources and physical parameters of the artificial light that induces changes in responses were not addressed to better comprehend the light-polluted scenarios that varied organism groups are exposed to [272]. Recently, Hölker et al addressed fundamental knowledge gaps, ranging from basic challenges on how to standardize light measurements, through the multi-level impacts on biodiversity, to opportunities and challenges for more sustainable use [273]. All these reviews gather crucial evidence on the night-time environment as a temporal niche in an ALAN context.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations